Uncovering the diversity of the neotropical genus Elaphopsocus (‘Psocoptera’: Psocidae: Amphigerontiinae): from one to ten species - Román-Palacios, Cristian; Obando, Ranulfo González; Aldrete, Alfonso N. García (Zootaxa, 2016)
For 75 years, the genus Elaphopsocus was considered a monotypic lineage of neotropical psocids. As a result of recent work in South America, this genus presently includes seven species from Brazil and Colombia. We here describe three new species from the East Colombian high Andes.